Neurophyseta (Lepidoptera: Crambidae) de Costa Rica - Phillips R, Eugenie; Solís, M Alma (Revista de Biología Tropical, 1996)
In this redescription of the genus Neurophyseta Hampson, 18 species from Costa Rica are revíewed and ilIustrated, and seven new species are described: albinalis Hampson; arcuatalis Hampson; conantia sp. nov.; clymenalis (Walker); cyclicalis Schaus; debalis (Druce); jessica sp. nov.; marin sp. nov.; mollitalis (Schaus); pomperialis (Druce); purifactalis (Dyar); randalis (Druce); renata sp. nov.; rufalis Hampson; sittenfelda sp. nov.; turrialbalis Schaus; vil/arda sp. nov. and zobeida sp. nov. In additíon, the diagnoses of Neurophyseta and the new species, and the key to the identífication of the males of the Costa Rican species are provided in English and Spanish.